Vermicomposting of mustard residue and effect of its application on soil and plant nutrients status. (14th December 2011) - Shilpkar, Prateek; Bhandari, S.C.; Rawat, U.S.; Shilpkar, Deepti
Vermicomposting of mustard (Brassica juncea) residue with pretreatments of submergence in water, nutrients (urea and low grade rock phosphate) supplementation, microbial (Bacillus sp., Trichoderma viride and Cellulomonas fimi) inoculation and their combined use with fresh cow dung/slurry improved the quality of vermicomposts with respect to C/N ratio, yield, humus fractions and nutrients content. These vermicomposts were then evaluated in a pot study for their direct as well as residual effect on crops growth at 0.25, 0.50 and 1.0% (w/w), using wheat as the main crop and green gram as the residual crop. The best quality of vermicompost with respect to its C/N ratio, humus fractions and nutrients content and to yield and nutrients uptake by crops and nutrients content in soil was obtained with the use of 5% urea, 5% low grade rock phosphate and microbial inoculation in combination with fresh cow dung.